Orbital Apex Lesions: A Diagnostic and Therapeutic Challenge - Cho, Sung-Woo; Lee, Won-Wook; Ma, Dae Joong; Kim, Ji-hoon; Han, Doo Hee; Kim, Hyun Jik; Kim, Dong-Young; Kim, Seong-Joon; Khwarg, Sang In; Kim, Sung-Min; Paek, Sun Ha; Rhee, Chae-Seo; Lee, Chul Hee; Hwang, Peter H.; Won, Tae-Bin (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objective To analyze the clinical characteristics of and treatment outcomes for orbital apex lesions according to their pathological diagnosis and identify clinical characteristics that could aid in their differential diagnosis.Design Retrospective analysis design was used for this study.Setting The study was conducted in a single tertiary institution.Participants Patients with pathologically confirmed lesions centered in the orbital apex who were admitted between January 2011 and December 2015.Main Outcome Measures Clinical characteristics, including demographics, predisposing factors, presenting symptoms, radiological findings, intraoperative findings, biopsy results, and treatment outcomes.Results Nine patients with invasive fungal sinusitis, six with inflammatory pseudotumor, and six with neoplastic or tumorous lesions were enrolled. The most common presenting symptom was orbital pain or headache, followed by ophthalmoplegia and vision loss, which exhibited overall recovery rates of 62.5% and 33.3%, respectively, after definitive treatment. The prognosis was worse for patients with invasive fungal sinusitis. There was no significant difference in age, underlying medical conditions, absolute neutrophil count, C-reactive protein level, and radiological findings among the three groups. Grossly necrotic tissues around the orbital apex area at biopsy were more frequently found in patients with invasive fungal sinusitis than in the other patients. In most cases, pain ameliorated after surgical intervention. There were no surgery-related morbidities.Conclusions Lesions centered in the orbital apex included invasive fungal sinusitis, inflammatory pseudotumor, and tumorous lesions. However, clinical features that clearly differentiated chronic invasive fungal sinusitis from inflammatory pseudotumor could not be identified. Our findings suggest that prompt biopsy is warranted for timely diagnosis, symptom relief, and early implementation of definitive treatment.
Keywords: orbital apex; invasive fungal sinusitis; inflammatory pseudotumor; biopsy; prognosis